Flexibility training - Brandon, R.
Flexibility training, or stretching, is used in varying forms by practically every coach, athlete and physiotherapist on a regular basis. That is to say, a form of stretching is likely to take place at some point in every training or therapy session. In spite of this, flexibility training is probably the least understood of all the fitness components, in terms of its scientific basis. This article will discuss the latest research findings and recommendations to explain why and how stretching should best be carried out.